Analysis of the Performance of Regional Original Revenue in Morowali Regency - Yulita Mahmud; Rian Risendy (Manunggal Halim Jaya, 2026)
Regional autonomy requires local governments to possess adequate financial capacity to support sustainable development. Local Own-Source Revenue (PAD) serves as a key indicator in assessing financial performance and the level of fiscal independence. This study aims to analyze the performance of PAD in Kabupaten Morowali during the 2020–2024 period and examine its impact on regional development, particularly in infrastructure, public services, and community welfare. This research employs a descriptive qualitative method, with data collected through in-depth interviews, observation, documentation, and analysis of the Regional Budget Realization Reports (LRA). The findings indicate that PAD performance shows an increasing trend, especially in 2023 and 2024, reflected in high effectiveness and growth ratios. However, the level of fiscal independence remains fluctuating and, in certain years, demonstrates dependence on intergovernmental transfer funds. The improvement in PAD has contributed positively to regional development, particularly in financing infrastructure and enhancing the quality of public services, although the impact has not been evenly distributed. Supporting factors for PAD optimization include strong regional economic potential, industrial sector growth, and local government commitment. Meanwhile, inhibiting factors consist of limited human resources, low taxpayer compliance, and reliance on transfer revenues. In conclusion, PAD plays a strategic role in supporting regional development; however, improvements in management quality and revenue collection efficiency are necessary to strengthen fiscal independence.